Comparison of Lapidus procedure fixation methods for hallux valgus: a 10-year retrospective analysis - Daniel, Akshatha; Peaty, James (International Journal of Research in Orthopaedics, 2023)
Background: The purpose of this study was to identify the type of Lapidus fixation method used in Leeds Teaching Trust Hospital that produces the best post-operative radiographical measurements. Methods: Thirty-five patients who underwent the Lapidus procedure were reviewed. Pre-operative and post-operative X-rays were measured to obtain angles; hallux valgus angle (HVA), first intermetatarsal angle (IMA), distal metatarsal articulate angle (DMA), meary angle (MA), and metatarsal declination angle (MDA). The fixation groups compared were dorso-medial plate vs dorsal plate vs medial plate and plate-single screw versus plate-crossed screw. The change in angle (Δ-angles) between pre-operative and post-operative were measured and the groups were compared. The fixation method that resulted in the largest Δ-angles and is statistically significant will be regarded as a superior fixation type within that group. Results: Groups with plate-single screw fixation showed a statistically significant (p<0.05) larger change in distal metatarsal articulate angle compared to plate-crossed screw fixation. Dorso-medial plate showed largest Δ-angles in the plate group although none were statistically significant. Conclusions: Fixation systems with single-screw result in better radiographical measurements compared to crossed-screws, significantly with the distal metatarsal articular angle. Dorso-medial plates result in better radiographical measurements followed by dorsal plate and then medial plate. However, these findings need validation with a randomized controlled trial before being generalized.